The Power of Sponges: Comparing High-Tech and Low-Tech Gaming for Innovation. (October 2015) - Meijer, Sebastiaan
Background .Innovation in transport systems has a need forsimulated environments toexperiment with new configurations, ideas, and solutions. Gaming is one such environment. This article applies the approach to thecontext of capacity allocation and traffic control innovation in the Dutch railway system.Both high-tech and low-tech games are built and applied. Aim and method . Bycomparing cases using low-tech and high-tech games for innovation in a relatedbundle of projects in the railway sector, this article aims to identifydifferent patterns emerging from a retrospective cross case comparison. The cases aimed at testing and assessing various ideas about the innovation process through high- and low-tech gaming. Results . Thehigh-tech cases were used to generate morequantitative data, for purposes where aconcept had to be tested that has been formulated at ahigher level of detail . It shows that, despite the higher precision, fidelity of high-tech simulators wasnot necessarily better than that of low-tech cases.None of the cases were set up to formally accept or rejecthypotheses, but followed the typical innovation logic oftesting and assessing ideas early in the process. Conclusions . Thenumerous qualitative data, gathered during the gaming sessions, illustrated the benefits and drawbacks of high- and low-tech gaming. Thereal world decisions made by the client, based on the gaming sessions, show that thescope of the project wasbroader than merely anintervention in an existing transport system.Low-tech games showed to be useful for dealing withrapid systems development (prototyping). They allowflexible role settings, varying rules, and resources.High-tech games didnot provide obviousfidelity advantages, but yieldedmore quantitative data suitable for analysis. Recommendations . The article identifies the need for anew methodological approach : gaming supportingsystem/organization design .